Enantiospecific synthesis of the sugar amino acid (2S,5S)-5-(aminomethyl)-tetrahydrofuran-2-carboxylic acid - Uhrig, Maria Laura (2010)
An enantiospecific synthesis of the tetrahydrofuran amino acid (2S,5S)-5-(aminomethyl)-tetrahydrofuran-2-carboxylic acid 1 is reported. The sugar enone 2-(S)-octyl 6-O-acetyl-3,4-dideoxy-a-D-glycerohex-3-enopyranosid-2-ulose 2a, derived from galactose, was employed as a chiral precursor. The enone 2a was converted by chemical manipulation of the functional groups into the 6-azido-2-O-tosyl-3,4,6-trideoxy-D-erythro-hexono-1,5-lactone 9 as key intermediate. Methanolysis of 9 induced the opening of the lactone and the attack of the hydroxyl group at C-5 to C-2 with the displacement of the tosylate. This reaction led to the formation of the tetrahydrofuran ring of methyl (2S,5S)-5-(azidomethyl)-tetrahydrofuran-2-carboxylate 10, which was readily converted into 1. The overall yield of the sequence was 35%, and all the intermediates and the final product have been fully characterized. In addition, the preferential conformations in solution of lactone 9 and target molecule 1 have been stablished.